First records of interstitial leptocytherids (Crustacea, Ostracoda): two new species and a redescription of Callistocythere ventricostata Ruan & Hao, 1988 collected from the Okinawa Islands, southern Japan - Ha, Tran Manh; Tsukagoshi, Akira (Zootaxa, 2015)
Two new and one known species belonging to the genus Callistocythere of the family Leptocytheridae from interstitial environments of the Okinawa Islands are fully described. Callistocythere intermedia sp. nov. is regarded as belonging to the C. japonica group, and Callistocythere ryukyuensis sp. nov. belongs to the C. minor group (these groups were established by Hanai 1957 based on carapace morphology). The redescribed Callistocythere ventricostata Ruan & Hao, 1988 clearly differs from known leptocytherid species in the morphologies of the carapace and the male copulatory organ. The habitats of C. intermedia sp. nov. and C. ryukyuensis sp. nov. are found along the shoreline zone and the mid to high tide levels of the littoral zone, respectively, and C. ventricostata is found from the shoreline to the sub-tidal zone. These species are the first global records of interstitial leptocytherids.